Empowering women across gender and caste in a women’s dairy cooperative in India - Farnworth, Cathy Rozel; Ravichandran, T.; Galiè, Alessandra (Frontiers Media, 2023)
Mulukanoor Women’s Dairy Cooperative (Mulukanoor Dairy) in India has been run by women for women since 2002. From the beginning it created strategies to empower women members, including mixing milk provided by the marginalized caste with milk from other castes; paying women exclusively for milk; providing technical training to women; and seating women together in training and governance events. Caste norms are not observed in these interactions. This article examines the effectiveness of Mulukanoor Dairy’s strategies for overcoming gender and caste disadvantage through empirical research. We hypothesized that if women members of Mulukanoor Dairy had become empowered over the past 20 years we should be able to see evidence for this in the form of women’s empowerment in relation to dairy decision-making at intra-household level. And if caste divisions had been largely overcome we should observe collegial relationships among women of different castes, and similar levels of women’s empowerment at intra-household level regardless of caste. Research was carried out in four villages provisioning Mulukanoor Dairy through focus group discussions with women members of Mulukanoor Dairy, and men spouses of different women members. In total 21 women and 23 men participated. FGDs were sex-and caste disaggregated. The introduction of a new sorghum forage, CoFS-29, provided the entry point to start talking about gender and caste norms. The findings show a remarkable transition of the dairy industry from elite non-marginalized caste men to marginalized and non-marginalized women. Caste norms have changed within the safe space of Mulukanoor Dairy and to a limited extent in the community. A new norm has been instituted that marginalized caste women are dairy farmers. Women across caste experience considerable decision-making power over milk and dairy income. However, men remain primary decision-makers over whether forage is grown. Men engage with key dairy chain actors. Knowledge on new technologies is passed only within castes, and mostly between persons of the same gender. Over the process of knowledge transmission, knowledge networks become increasingly masculinized. Knowledge networks are stronger among non-marginalized men who are best able to make use of new technologies.